The Impact of Employer Branding on Turnover Intention in Pharmaceutical Industries: Does Generation Matter? - Ivana Gracita; Rina Anindita (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
In an increasingly globalized economy, organizations are increasingly competing for the best employees who are skilled in professional fields. Employer branding has an important role in helping organizations find new employees and retain existing employees. The goal of this study was to look at the effect of employer branding on organizational commitment and turnover intention in the pharmaceutical industry, as it was moderated by generation. The population sample is made up of Generation X, Y, and Z workers in the pharmaceutical industries in Indonesia. The sampling technique uses a non-probability sampling method with purposive sampling. PLS-SEM was utilized in this study to analyze data from 175 samples. The research results have proven that employer branding increases organizational commitment and decreases turnover intention. Organizational commitment reduces turnover intention. Moreover, the relationship between employer branding and turnover intention might be mediated by organizational commitment. The association between organizational commitment and turnover intention or employer branding and turnover intention cannot be moderated by generation because it has no impact on turnover intention in the pharmaceutical industries. Corporate leaders need to establish and develop employer branding to increase organizational commitment and reduce turnover intentions in the pharmaceutical industry.